Diversity of Birds at the Romokalisari Adventure Land Tourist Attraction Surabaya - Effendi, Alya Anggraini; Kurniawan, Eka Resi; Ambarwati, Reni; Gumilang, Ragil Satriyo (LenteraBio : Berkala Ilmiah Biologi, 2025)
Waterbirds are a type of bird that is ecologically dependent on wetlands. The distribution and population of birds in a habitat are influenced by physical or environmental factors such as soil, air, temperature, sunlight, and biological factors including vegetation and other animals. This study aims to analyzed bird diversity and conservation status at Romokalisari Adventure Land, Surabaya. The Romokalisari Adventure Land Surabaya is one of the tourist attractions in Surabaya that offers a mangrove forest area as the landscape. The study were conducted in February 2024. Observation activities began at 06.30-10.00 WIB using the line transect method across three transects of 1.000 meters each, identifying bird species through direct observation and photographic documentation. The number, abundance, and diversity of birds in their habitat are caused by complex ecological interactions and are closely related to the bird community. Whereas Shannon-Wiener diversity index (H’) used to determine species diversity index. The bird diversity index value at the Romokalisari Adventure Land is classified as moderate. As a result, 15 species from 10 families of birds were found, 1 species of bird is classified as Endangered based on IUCN Red List, namely the Milky Stork and 6 species of water birds with national protection status. The study emphasizes the importance of preserving mangrove ecosystems as they serve as critical habitats for various bird species.